2012
DOI: 10.1242/jeb.064055
|View full text |Cite
|
Sign up to set email alerts
|

Muscular tissues of the squid Doryteuthis pealeii express identical myosin heavy chain isoforms: an alternative mechanism for tuning contractile speed

Abstract: SUMMARYThe speed of muscle contraction is largely controlled at the sarcomere level by the ATPase activity of the motor protein myosin. Differences in amino acid sequence in catalytically important regions of myosin yield different myosin isoforms with varying ATPase activities and resulting differences in cross-bridge cycling rates and interfilamentary sliding velocities. Modulation of whole-muscle performance by changes in myosin isoform ATPase activity is regarded as a universal mechanism to tune contractil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…In conclusion, we have shown that S. officinalis and O. bimaculoides , like the squid D. pealeii (Shaffer & Kier ), do not appear to express tissue‐specific myosin heavy chain isoforms. Although additional work is needed, these results suggest that coleoid cephalopods in general may use ultrastructural differences, primarily variation in thick filament length, to tune contractile velocity.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In conclusion, we have shown that S. officinalis and O. bimaculoides , like the squid D. pealeii (Shaffer & Kier ), do not appear to express tissue‐specific myosin heavy chain isoforms. Although additional work is needed, these results suggest that coleoid cephalopods in general may use ultrastructural differences, primarily variation in thick filament length, to tune contractile velocity.…”
Section: Discussionmentioning
confidence: 67%
“…), so a functional difference, if any, would not affect function in a tissue‐specific manner. A final possibility is that the squid also expresses more than three myosin heavy chain isoforms, but that they were missed in the previous study by Shaffer & Kier (). While possible, we think that it is unlikely due to the large number of samples prepared and sequenced over the course of the study.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Squid modulate isometric force and shortening velocity by varying thick filament length, not by expressing different isoforms of myosin heavy chain (Kier and Schachat, 1992;Kier and Schachat, 2008;Thompson et al, 2010b;Shaffer and Kier, 2012). Although other myofilament lattice proteins have the potential to affect the length-force relationship as well (e.g.…”
Section: Mantle Kinematics and In Vivo Muscle Operating Length Rangementioning
confidence: 99%